The capabilities of honeycomb core structures made of kenaf/polylactic acid composite under compression loading - Yusri, M. A. H. M.; Zuhri, M. Y. M.; Ishak, M. R.; Azman, M. A. (Multidisciplinary Digital Publishing Institute, 2023)
This study investigated the capability of honeycomb core structures made of kenaf fibrereinforced polylactic acid (PLA) composite. Two types of kenaf fibre were used in this study, these being woven kenaf and non-woven cotton/kenaf. Initially, the corrugated shape panel was manufactured using a hot moulding compression method. The panel was then cut into corrugated strips, bonded together using epoxy resin to form the honeycomb core structure, and balsa wood used as their skins. The effects of core height and crosshead displacement rate were investigated. The honeycomb core consisted of 20 mm, 30 mm and 40 mm core heights, and the crosshead displacement rate ranged from 2 mm/min to 500 min/min. Of all the samples, core structure with a height of 20 mm tested at 500 mm/min offered the highest value of compressive strength and specific energy absorption, which were 6.23 MPa and 12.36 kJ/kg, respectively. It was also discovered that the core height and loading rate have significant effects on the mechanical properties of the kenaf/PLA honeycomb core structure.